Long waitlists for outpatient drug allergy referrals: An Australian tertiary centre experience - Syed Ali, MBBS, FRACP; Tiffany Hughes, MBBS, FRACP; Anthony Smith, MBBS, FRACP, PhD (World Allergy Organization Journal, 2024)
Drug allergy clinic waitlist time data are limited. A 24-month retrospective study of drug allergy referrals was undertaken at a tertiary hospital in Australia. One hundred six patients were reviewed with a median age of 50 years (IQR 40.5–67.3) and a female predominance (n = 76, 71%). Face-to-face consultations were common (n = 83, 78.3%) with the remainder being telephone consultations.General practitioners comprised just over one-third (n = 38, 35.9%) of the referrers but majority being from within the hospital, such as the emergency department (n = 22, 20.8%). Most patients (n = 100, 94.3%) were triaged as Category 1 or urgent. Antibiotic allergies were common (n = 75, 70.8%), of which majority were beta-lactam antibiotics (n = 71, 95%): 55 (73.3%) for penicillins and 16 (15.1%) for cephalosporins.The median waitlist time was 178 days (IQR 48.5–502.5) and only 18 (17%) of Category 1 were seen within urgent timeframe. Telephone consultation had a significantly shorter waitlist time (median 47 days; IQR 6–245) compared to face-to-face consultations (median 267 days; IQR 69–519) (p = 0.026).Large waitlist times are present for drug allergy, and given the majority of referrers are from hospitals, inpatient drug allergy assessment remains paramount. Beta-lactam antibiotic drug allergy labels remain common, and given their negative implications, further work is needed. Economic and human resources evaluations are required to address this shortfall.